An Ad5-vectored platform generating self-assembling VLPs elicits potent mucosal immunity against influenza A virus and SARS-CoV-2 - Yuan Zhang; Caiqian Wang; Yanhong Zheng; Feiyu Chen; Yaya Feng; Lingying Fang; Zongmei Wang; Ming Zhou; Zhen F. Fu; Ling Zhao (Proceedings of the National Academy of Sciences, 2026)
Integrating complementary vaccine modalities is essential for combating emerging pathogens. Although the recent mRNA-VLP hybrids enable spontaneous virus-like particles (VLPs) self-assembly, thereby enhancing immunogenicity, they fail to elicit robust pulmonary mucosal immunity against respiratory pathogens. Here, we developed Ad5-Envp-VLP, a chimeric adenoviral platform enabling spontaneous in vivo assembly of envelope protein-displaying VLPs using advanced technology that recruits ESCRT (endosomal sorting complex required for transport) via the EABR (ESCRT and ALIX-binding region). Compared with the intramuscular route, intranasal administration of a single-dose Ad5-HA-VLP confers long-lasting protection against both homologous and heterologous influenza A strains. Integrated single-cell RNA sequencing and flow cytometry analyses reveal that intranasal delivery of Ad5-HA-VLP recruits and functionally reprograms lung innate immune cells, promoting antigen presentation and driving robust mucosal secretory IgA (sIgA) secretion and cytotoxic T lymphocyte responses. Similarly, intranasal delivery of Ad5-S-VLP elicits potent cross-neutralizing antibody titers against SARS-CoV-2 variants. Importantly, intranasal immunization with Ad5-S-HA-VLP (coexpressing S- and HA-VLPs) generates dual influenza and SARS-CoV-2 neutralizing antibodies, alongside pulmonary antigen-specific sIgA, confirming Ad5-Envp-VLP as a promising “single-dose multiplexed mucosal vaccine” against respiratory pathogens. Further extended applications show that Ad5-RVDG-VLP also induces broad protective immunity in mouse, dog, and cat models, verifying its feasibility as an efficient rabies vaccine. Collectively, the Ad5-Envp-VLP platform represents a universal and versatile mucosal vaccine strategy, leveraging pulmonary delivery of vectors that encode in vivo-assembling VLPs to concurrently elicit robust mucosal and systemic immunity against a wide spectrum of pathogens.